Pore development characteristics and main controlling factors of tight oil reservoir in the seventh member of Triassic Yanchang Formation, Xunyi area, Ordos Basin - Liangjun WANG; Xinxin YUE; Liansheng LI; Yanpeng WANG (Shiyou shiyan dizhi)
The seventh member of the Triassic Yanchang Formation (Chang 7 Member) in the Xunyi area of the Ordos Basin is a typical tight oil reservoir characterized by low porosity, low permeability, and strong heterogeneity. Elucidating the pore development characteristics and primary controlling factors of the reservoir is beneficial for tight oil exploration and development. Through thin-section analysis, physical property tests, scanning electron microscopy(SEM), X-ray diffraction (XRD) analysis, and mercury intrusion porosimetry, this study investigated the petrological characteristics, reservoir space, and diagenetic evolution of the tight oil reservoir, revealing its main controlling factors. The reservoir depth in Chang 7 Member of the Xunyi area of the Ordos Basin ranged from 500 to 1 250 m. The lithology was primarily composed of lithic arkose sandstone, followed by feldspar lithic sandstone, with the interstitial materials mainly consisting of calcite, dolomite, and mud. The sand bodies in the reservoir were thick, with high compositional maturity. Rigid minerals, such as quartz and feldspar, which are highly resistant to weathering, made up a large portion of the framework grains. The quartz content ranged from 30% to 77%, with an average of 44.97%, while the feldspar content ranged from 4% to 52%, with an average of 31.61%. The pore types were mostly intergranular dissolved pores and intragranular dissolved pores, followed by residual intergranular pores and a few microfractures. The average porosity was 7.3%, and the average permeability was 0.4×10-3 μm2. The reservoir is in the middle diagenetic stage A and has completed tight compaction during the Cretaceous. The primary factors contributing to reservoir densification included its poor resistance to compaction, carbonate cementation, illite/smectite mixed layers, and authigenic quartz. The quartz and feldspar content and early oil and gas charging preserved a significant quantity of primary pores. The ongoing dissolution and fragmentation during the middle diagenetic stage were the primary causes for the development of secondary pores.